Influence of the aspect ratio on seismic performance of adobe buildings - Otero Monteza, Danty Alexander (2022)
Adobe buildings usually are characterized by having walls with small and uniform slenderness ratios; nevertheless, there are some historical adobe buildings with existing large walls, where the influence of the aspect ratio becomes quite important in the seismic behavior. This article analyzes the seismic behavior of adobe buildings with larger walls in one axis than the other orthogonal axis. Also, the influence of the aspect ratio of the wall height respects on the wall length is analyzed by varying the wall length. Finite element models were elaborated using the concrete damaged plasticity model to study the influence of the aspect ratio on the seismic behavior of adobe buildings. Four models of buildings having different aspect ratios, varying in length from eight meters to fifty-two meters have been considered. Nonlinear time history analyses with three Peruvian seismic records are conducted. Regarding material, information was collected on the parameters necessary for finite element modeling for adobe masonry. From the non-linear simulations, the cracking patterns of the four buildings were identified. The influence of the aspect ratio in the seismic capacity of these kind of adobe buildings is analyzed.  Finally, the results obtained in the numerical models are compared with the evidence of damage caused by past earthquakes.